2016
DOI: 10.1038/srep19600
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bacterial diversity in two oil blocks from two low-permeability reservoirs with high salinities

Abstract: The community diversities of two oil reservoirs with low permeability of 1.81 × 10−3 and 2.29 × 10−3 μm2 in Changqing, China, were investigated using a high throughput sequencing technique to analyze the influence of biostimulation with a nutrient activator on the bacterial communities. These two blocks differed significantly in salinity (average 17,500 vs 40,900 mg/L). A core simulation test was used to evaluate the effectiveness of indigenous microbial-enhanced oil recovery (MEOR). The results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 36 publications
2
14
0
1
Order By: Relevance
“…However, the extreme environment of oil wells (i.e., high temperature, salinity and pressure) is proposed to favor the growth of indigenous bacterial communities and depress foreign species (Wang et al, 2014). Furthermore, our results are in agreement with previous reports on microbial diversity in other oil well reserves (Lenchi et al, 2013;Xiao et al, 2016). The biosurfactant-producing bacteria identified in this study (Bacillus, Streptomyces, Microbacterium Pseudomonas, Arthrobacter, Rhodococcus and Micrococcus) belong to genera that have also been identified in a wide range of studies as crude oil degraders and biosurfactant producers (Wu et al, 2008;Brooijmans et al, 2009;Korenblum et al, 2012;Obi et al, 2016;Parthipan et al, 2017;Xu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…However, the extreme environment of oil wells (i.e., high temperature, salinity and pressure) is proposed to favor the growth of indigenous bacterial communities and depress foreign species (Wang et al, 2014). Furthermore, our results are in agreement with previous reports on microbial diversity in other oil well reserves (Lenchi et al, 2013;Xiao et al, 2016). The biosurfactant-producing bacteria identified in this study (Bacillus, Streptomyces, Microbacterium Pseudomonas, Arthrobacter, Rhodococcus and Micrococcus) belong to genera that have also been identified in a wide range of studies as crude oil degraders and biosurfactant producers (Wu et al, 2008;Brooijmans et al, 2009;Korenblum et al, 2012;Obi et al, 2016;Parthipan et al, 2017;Xu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The microbial community composition showed similarities in the three tested oil seeps and the calculated low Shannon-Wiener and high Simpson diversity indices are similar to other oil field microbial communities (45)(46)(47)(48). Such values may reflect a high specialization and a long isolation of the community, leading to reduced diversity but evenly composed microbial communities in the three sampled oil seeps.…”
Section: Discussionsupporting
confidence: 60%
“…The detected SRB were affiliated to Deltaproteobacteria and Clostridia , while most microbes assigned to SOB were affiliated to Beta- , Alpha- and Epsilonproteobacteria which were found in many studies as is shown in Figures 3C,D ( Belila et al, 2013 ; Guan et al, 2013 ; Headd and Engel, 2013 ; Gao et al, 2015a ). Among petroleum reservoirs, SRB and SOB communities exerted niche specificity and showed strong relationships to reservoir physicochemical factors which play an important role in shift the microbial community, like temperature, PH and the concentration of various ions ( Zhang et al, 2010 , 2012 ; Xia et al, 2014 ; Xiao et al, 2016 ). Communities among different reservoirs were affected by different environmental variables, while SRB and SOB were influenced by same environmental variables in each reservoir.…”
Section: Discussionmentioning
confidence: 99%